ANT and Engineering Education, learning spaces with actors - Figueiredo, Jose (Advances in Social Sciences Research Journal, 2020)
Engineering education is a situated process, enacted by empowerment, motivation and enrolment of actors, using different materials, and framed in exploratory attempts. Inscribing technologic design in the use of artefacts is a basic engineering concern and pushes us to sociotechnical ambiences of value earning and sustainability. We think Actor-Network Theory provides a framework that contributes to our understanding of complexity inscribed in the relations and mutual influences that emerge among actors in learning spaces. Using narrative, and exploring ANT concepts, we circulate in learning spaces, observing and deciding about ways we can explore to enhance knowledge creation and learning. Our results are exploratory but they intend to contribute to a different look into educational fields. Our basic goal is to convince researchers to join us in our reflections and experiments. We believe we are tackling with an innovative perspective, consistent with an extension to this area of knowledge – engineering education.